Effectiveness of Flipped Learning Instructional Pedagogy on Learning Engagement and Academic Achievement in Chemistry - M, Vandana; Taj, Haseen (JOURNAL OF INDIAN EDUCATION, 2022)
Innovative pedagogies of the digital age attempts to abandon the passive teacher centred one way teaching process involving students actively to facilitate learning, thus improving the teaching-learning process. Flipped instruction is a digital pedagogy which has brought drastic changes in the teaching-learning process which reverses the traditional learning environment and students invest their time and effort in both synchronous and asynchronous sessions. Hence, in this experimental study the researcher attempted to investigate the effectiveness of flipped instruction on students’ learning engagement and academic achievement by collecting data from Grade IX students and the analysis showed that there is significant difference in Learning Engagement and Academic Achievement in Chemistry of students who were taught using flipped learning instruction and traditional learning, further, the students taught with flipped learning instruction had better learning engagement and higher achievement scores compared to the students taught with traditional learning mode.